2017
DOI: 10.4103/eus.eus_2_17
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound with or without fine-needle aspiration has a meaningful impact on clinical care in the pediatric population

Abstract: Background and Objectives:The safety and utility of endoscopic ultrasound (EUS) for the evaluation and management of gastrointestinal (GI) tract disorders among adults has been established. The literature on safety and efficacy in a pediatric referral population (under 21 years of age) is limited. We hypothesized that EUS is safe and useful in the pediatric population. We reviewed the pediatric EUS experience at a single tertiary-care system. We describe the indications, findings, safety, technical success rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
(25 reference statements)
0
14
0
1
Order By: Relevance
“…Therapeutic EUS was performed in 16 cases (7 pancreatic pseudocyst drainage, 7 celiac plexus block, 1 EUS-guided transgastric biliary drainage[ 4 , 6 - 8 , 15 , 16 ] and 1 mediastinal bronchogenic cyst aspiration in our study). The incidence rate of EUS-related complications ranged between 1.96% and 7.1%; which was reported in only 4 studies[ 3 , 4 , 6 , 16 ]. Complications included mild pancreatitis after FNA of solid pancreatic lesions, fever and bleeding after EUS-guided cystogastrostomy and anesthesia-related complications (hypoxia due to airway obstruction and laryngospasm).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Therapeutic EUS was performed in 16 cases (7 pancreatic pseudocyst drainage, 7 celiac plexus block, 1 EUS-guided transgastric biliary drainage[ 4 , 6 - 8 , 15 , 16 ] and 1 mediastinal bronchogenic cyst aspiration in our study). The incidence rate of EUS-related complications ranged between 1.96% and 7.1%; which was reported in only 4 studies[ 3 , 4 , 6 , 16 ]. Complications included mild pancreatitis after FNA of solid pancreatic lesions, fever and bleeding after EUS-guided cystogastrostomy and anesthesia-related complications (hypoxia due to airway obstruction and laryngospasm).…”
Section: Discussionmentioning
confidence: 94%
“…This was comparable to the study by Varadarajulu et al[ 10 ], who reported that EUS had a significant impact on the clinical care of 13 out of 14 patients (93%) with pancreaticobiliary disorders. Similarly, Raina et al[ 16 ] reported a significant impact on clinical care in 88% of cases and AlRashdan et al[ 7 ] reported a different diagnosis achieved by EUS in 86% of cases. These data suggest that EUS when performed by expert endosonographers is safe, feasible, and has a significant impact on the clinical care of pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…При этом авторы сходятся во мнении, что эндо-УЗИ оказалось полезным методом, в подавляющем большинстве наблюдений оказавшим влияние на выбор или изменение тактики лечения (табл. 2) [13][14][15][16][17].…”
Section: Discussionunclassified